Fashion Drives Impulsive Buying in Indonesia: Fesyen Mendorong Pembelian Impulsif di Indonesia - Pramana, Sugianto Eko; Indayani, Lilik; Febriansyah, Rizky Eka (Indonesian Journal of Law and Economics Review, 2024)
This research explores how Fashion Involvement and Shopping Lifestyle influence Impulsive Buying at the Eiger Store in Sidoarjo. Using a quantitative survey method, data were collected from 100 respondents via Google Forms and analyzed with SPSS. Results indicate that both Fashion Involvement and Shopping Lifestyle significantly and positively impact Impulsive Buying, with Fashion Involvement having a stronger influence. Key findings suggest that Eiger Store should enhance online sales and update sales strategies for new fashion models to attract more customers. These insights can guide targeted marketing strategies to increase impulsive buying behavior. Highlight: Fashion Involvement strongly influences impulsive buying. Enhance online sales for busy Sidoarjo residents. Update strategies for new fashion models to attract customers. Keyword: Impulsive Buying, Fashion Involvement, Shopping Lifestyle, Consumer Behavior, Eiger Store